THE EFFECT OF LAVENDER AROMA THERAPY ON THE SLEEP QUALITY OF PREGNANT WOMEN TM III - Rohmah, Hajar Nur Fathur (Jurnal MIDPRO, 2024)
Good quality sleep will maintain maternal health during pregnancy and provide maternal health by providing sufficient energy during labor. This has an impact on normal physiological changes during pregnancy such as increasing the size of the uterus, physical discomfort and increasing the hormone progesterone. The solution to improve the quality of mother's sleep is by providing lavender aromatherapy. This research is to prove the effect of lavender aromatherapy on third trimester pregnant women. The research design is quasi-experimental, pretest-posttest one group design approach. Population of all third trimester pregnant women in Bantarjaya Village, Pebayuran, Bekasi. Sampling was carried out using a purposive sampling technique with a total of 31 respondents. Sleep quality was measured using the PSQI questionnaire. The data obtained were analyzed using the paired sample t-test. The results of data analysis show that p value = 0.000. So the hypothesis in this study is accepted, namely that there is an influence of lavender aromatherapy on sleep quality in third trimester pregnant women. Based on research results, the use of lavender aromatherapy can be a safe choice for pregnant women to improve sleep quality.